Profluorescent substrates for the screening of olefin metathesis catalysts - Reuter, Raphael; Ward, Thomas R. (Beilstein Journal of Organic Chemistry, 2015)
Herein we report on a 96-well plate assay based on the fluorescence resulting from the ring-closing metathesis of two profluorophoric substrates. To demonstrate the validity of the approach, four commercially available ruthenium-metathesis catalysts were evaluated in six different solvents. The results from the fluorescent assay agree well with HPLC conversions, validating the usefulness of the approach.
Keywords: fluorescence; microplate screening; ring closing metathesis

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

Handbook of Metathesis - Grubbs, R. H. (Wiley-VCH, 2003)

(untitled) - Hoveyda, A. H.; Zhugralin, A. R. (Nature, 2007)

Olefin Metathesis: Theory and Practice - Bruneau, C.; Fischmeister, C. (Olefin Metathesis in Green Organic Solvents and without Solvent, 2014)

(untitled) - Schrock, R. R. (Acc. Chem. Res., 1990)

(untitled) - Leitgeb, A.; Wappel, J.; Slugovc, C. (Polymer, 2010)

(untitled) - Gradillas, A.; Pérez-Castells, J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Lo, C.; Ringenberg, M. R.; Gnandt, D.; Wilson, Y.; Ward, T. R. (Chem. Commun., 2011)

(untitled) - Mayer, C.; Gillingham, D. G.; Ward, T. R.; Hilvert, D. (Chem. Commun., 2011)

(untitled) - Philippart, F.; Arlt, M.; Gotzen, S.; Tenne, S.-J.; Bocola, M.; Chen, H.-H.; Zhu, L.; Schwaneberg, U.; Okuda, J. (Chem. – Eur. J., 2013)

(untitled) - Lin, Y. A.; Chalker, J. M.; Floyd, N.; Bernardes, G. J. L.; Davis, B. G. (J. Am. Chem. Soc., 2008)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Toomre, D.; Bewersdorf, J. (Annu. Rev. Cell Dev. Biol., 2010)

(untitled) - Yin, J.; Hu, Y.; Yoon, J. (Chem. Soc. Rev., 2015)

(untitled) - Godoy, J.; García-López, V.; Wang, L.-Y.; Rondeau-Gagné, S.; Link, S.; Martí, A. A.; Tour, J. M. (Tetrahedron, 2015)

(untitled) - Vorfalt, T.; Wannowius, K. J.; Thiel, V.; Plenio, H. (Chem. – Eur. J., 2010)

(untitled) - Agudelo-Morales, C. E.; Silva, O. F.; Galian, R. E.; Pérez-Prieto, J. (ChemPhysChem, 2012)

(untitled) - Timmer, M. S. M.; Codée, J. D. C.; Overkleeft, H. S.; van Boom, J. H.; van der Marel, G. A. (Synlett, 2004)

(untitled) - de Jong, A. R.; Volbeda, A. G.; Hagen, B.; van den Elst, H.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Eur. J. Org. Chem., 2013)

(untitled) - Chatterjee, A. K.; Toste, F. D.; Goldberg, S. D.; Grubbs, R. H. (Pure Appl. Chem., 2003)

(untitled) - Nguyen Van, T.; Debenedetti, S.; De Kimpe, N. (Tetrahedron Lett., 2003)

(untitled) - Xie, L.; Chen, Y.; Wu, W.; Guo, H.; Zhao, J.; Yu, X. (Dyes Pigm., 2012)

(untitled) - Kapeller, D. C.; Bräse, S. (ACS Comb. Sci., 2011)

(untitled) - Kajetanowicz, A.; Chatterjee, A.; Reuter, R.; Ward, T. R. (Catal. Lett., 2013)

(untitled) - Ogilvie, W.; Deziel, R.; O’Meara, J.; Simoneau, B. (Non-Nucleoside Reverse Transcriptase Inhibitors, 2003)

(untitled) - Yang, Y.; Babiak, P.; Reymond, J.-L. (Org. Biomol. Chem., 2006)

(untitled) - Schmidt, B.; Krehl, S. (Chem. Commun., 2011)